LABORATORY TESTING OF BENTONITE CLAYS FOR LANDFILL DESIGN AND CONSTRUCTION - Biljana Kovačević Zelić; Dubravko Domitrović; Želimir Veinović (Rudarsko-geološko-naftni Zbornik, 2007)
Top and bottom liners are one of the key construction elements in every landfill. They are usually made as compacted clay liners (CCLs) composed of several layers of compacted clay with strictly defined properties or by the use of alternative materials such as: GCL – geosynthetic clay liner, BES – bentonite enhanced soils or bentonite/polymer mixtures. Following the state of the art experiences in the world, GCLs are used in Croatian landfills for several years, as well. Depending upon the location and the obeying function, GCLs have to fulfill certain conditions. A legislated compatibility criterion has to be proven by various laboratory tests. In the paper are presented the results of direct shear and chemical compatibility tests of GCLs as well as the results of permeability measurement of kaolin clay (the paper is published in Croatian ).